Towards domain-independent conflict resolution tools - Carneiro, Davide Rua (2011)
Given the current state of the legal systems, Online Dispute Resolution tools are being regarded as an alternative way to solve conflicts out of courts, namely under virtual environments. However, the use of these tools is still relatively restricted as they are still few in number and very domain-cantered. Indeed, abstract and conceptual tools whose building blocks could be adapted for particular use would foster the development of ODR systems. In this paper we present this novel line of attack, in which an agent-based architecture is used with the support of an ontology to build an abstract and formal ODR system, independent of the legal domains, but specific enough to be applied to concrete ones. Functionality reuse is maximized, making architectures simpler to implement and to expand.